Garbage Bin Monitoring System using GSM - Abdul Halim, Muhammad Mustaqim (IRC, 2020)
In today’s era, garbage bins are not being properly cleaned. It involves garbage spill in resulting in land degradation, disease spread, as well as creating unhygienic conditions for humans, and ugliness to that area. The main issues for this matter are the garbage bins are not monitored. The process of monitoring garbage bins is challenging because there are too many garbage bins and the distance are far apart. Therefore, there is a need for monitoring system of the garbage bins. In this paper, a garbage bin monitoring system using GSM is developed. The garbage bin is embedded with an ultrasonic sensor to detect the level of the trash, and the data will be transmitted via SMS using GSM module. This garbage bin that was developed helps us to monitor the amount of waste filling by sending an alert via SMS to inform the filling status level. This project has been tested by three-level, which is 30%, 50% and 90%. The test cases were selected based on the practical ways of providing waste collection service. The system was tested experimentally for the defined test cases. The test has shown the effective garbage bin monitoring system using GSM by validating the defined test cases. This is shown that the garbage bin monitoring system using GSM could be a great resource in solid waste management.